Preparation and Purification of Copper Metal from Dross Scrap of the State Company for Electrical Industries by Electrochemical Technique. (مجلة بغداد للعلوم, 2013)
The copper metal was prepared and purified from dross scrap by electrochemical technique, using insoluble inert anode made of lead. The scrap was dissolved in 6M HCl. Cations of Al, Mn ,Ni, As, and Zn were separated by passing the solution of dross through strong basic anion exchanger (IRA 400) Column ,while the iron and copper were retained on column and then separated them by more dilute hydrochloric acid (0.005M) . Iron separated from copper by precipitating as basic ferric acetate and then heated to 600°C for one hour to obtain ferric oxide. Copper precipitated as copper nitrate hydroxide from acid solution at PH(4.5-5.5). The copper nitrate hydroxide has been recrystalized by ethanol and dionized water and then heated to 900°C for one hour to obtain copper oxide. The copper metal has been prepared from copper oxide by electrochemical technique. The copper nitrate hydroxide, aluminum hydroxide, copper oxide and pure copper have been  identified by X-ray diffraction (XRD),    X-ray fluorescence (XRF) and elemental analysis by using flame and flameless atomic absorption spectrophotometer techniques.